2018
DOI: 10.12659/msm.908839
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Renal Function in Children with Congenital Scoliosis and Congenital Anomalies of the Kidney and Urinary Tract

Abstract: BackgroundThe aim of this study was to compare renal function in children with congenital scoliosis and congenital anomalies of the kidney and urinary tract, with healthy children.Material/MethodsBiochemical tests were performed before surgery (pre-therapy) and after surgery (post-therapy) in 16 children with congenital scoliosis and congenital anomalies of the kidney and urinary tract. Thirty-two healthy children were matched for age, sex, and weight (healthy controls). General renal function tests included s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In contrast, Gao et al. reported that routine tests showed normal renal function in children with congenital scoliosis and congenital anomalies of the kidneys and urinary tract 23 . Therefore, the effects of scoliosis on renal function are controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Gao et al. reported that routine tests showed normal renal function in children with congenital scoliosis and congenital anomalies of the kidneys and urinary tract 23 . Therefore, the effects of scoliosis on renal function are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…22 In contrast, Gao et al reported that routine tests showed normal renal function in children with congenital scoliosis and congenital anomalies of the kidneys and urinary tract. 23 Therefore, the effects of scoliosis on renal function are controversial. The present results indicated that renal function was superior in NF1 patients than in the controls even though the prevalence of scoliosis was significantly higher in the former than in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al . found that the expression of B2M in the excreted urine was increased in the scoliosis children [ 21 ], and Suzuki et al . also found that increased excretion of B2M through urine in idiopathic scoliosis patients with urinary tract obstruction [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Thus, respiratory damage, including respiratory failure (RF), is a well-recognised complication of severe congenital spinal deformity. 4 RF is divided into types I and II, the former only showing a reduction of partial pressure of arterial oxygen (PaO 2) , while the latter is characterised by PaO 2 <60 mmHg and PaCO 2 >50 mmHg. Untreated patients can suffer from acute RF due to the gradual reduction of respiratory volume, and the incidence and intraoperative and postoperative mortality rates are high.…”
Section: Introductionmentioning
confidence: 99%